2017
DOI: 10.1515/pcard-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Myocardial Displacement and Tissue Velocity Analysis of the Right Ventricle in Hypoplastic Left Heart Syndrome Fetuses and Controls Using Color Tissue Doppler Imaging (C-TDI)

Abstract: Introduction: The long-term outcome of patients with HLHS (hypoplastic left heart syndrome) is mainly determined by right ventricular function. Our study examines, whether there are differences in segmental right ventricular myocardial displacement and tissue velocities of fetuses with HLHS compared to healthy fetuses during gestation.Materials and methods: A prospective study was conducted including 20 fetuses with HLHS and 20 gestational age matched controls. c-TDI (colour tissue Doppler imaging) derived sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In line with our findings, Al Subhi et al [6] perspective's analysis discovered that HLH fetus had greater E and A velocities (p =0.01). However, a prospective investigation by Graupner et al [11] indicated that compared to healthy fetus, the group with Hypoplastic Lt heart syndrome had significantly lower E′ velocities (p= 0.017) and E′/A′ ratios (p= 0.012) when right ventricular function was examined. A lower E/A ratio shows that atrial contraction is what drives the process of ventricular filling rather than the negative pressure experienced during relaxation.…”
Section: Discussionmentioning
confidence: 98%
“…In line with our findings, Al Subhi et al [6] perspective's analysis discovered that HLH fetus had greater E and A velocities (p =0.01). However, a prospective investigation by Graupner et al [11] indicated that compared to healthy fetus, the group with Hypoplastic Lt heart syndrome had significantly lower E′ velocities (p= 0.017) and E′/A′ ratios (p= 0.012) when right ventricular function was examined. A lower E/A ratio shows that atrial contraction is what drives the process of ventricular filling rather than the negative pressure experienced during relaxation.…”
Section: Discussionmentioning
confidence: 98%
“…The tissue Doppler technique (TDI) measures the speed of movement of the annuli of the atrioventricular valves during the heart cycle. The assessment of these velocities is an early and sensitive measure of systolic-diastolic dysfunction [10,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The speckle tracking technique allows the evaluation of myocardial deformation during systole and diastole (parameters such as "strain" and "strain rate" can be measured). Abnormal deformation of the heart muscle is an early symptom of its dysfunction [10,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%